Development of a simple calculation tool of dose distributions in a phantom for boron neutron capture therapy. (1st July 2022) - Ishikawa, Akihisa; Watanabe, Kenichi; Yoshihashi, Sachiko; Sakurai, Yoshinori; Kumada, Hiroaki; Tanaka, Hiroki; Uritani, Akira; Kiyanagi, Yoshiaki
Abstract: A simple dose calculation tool, SiDE, was developed for dose evaluation in a water phantom for boron neutron capture therapy, which makes the calculation time much shorter compared with the conventional particle transportation Monte Carlo codes and is applicable to any type of incident neutron spectra to the phantom. As the SiDE can not only calculate quantitatively the dose distribution in the phantom but also output dose indexes such as advantage depth and peak tumor dose, a comparison between different boron neutron capture therapy neutron sources can be easily performed. Consistency with a Monte Carlo transportation code was verified through comparison with the conventional dose calculation with the Particle and Heavy Ion Transport Code System, and the calculation time was nearly 1/90 in the SiDE. The dose distributions for a reactor and accelerator-based neutron sources were compared, and the differences were found to be small although large differences existed between the incident spectra.